Investigating Freshmen's Perceptions of Using Authentic Materials in Reading Classes at Sai Gon University - Trinh, Le Thi Thuy; Tam, Tran Pham My (IPI Garut Press, 2025)
Authentic Materials, defined as resources created for native speakers, provide contextualized language exposure that traditional materials often lack. Especially when authentic materials are integrated into educational settings through classes. Therefore, exploring students' perceptions of using Authentic Materials in reading classes is a research topic of interest. This paper examines the perceptions and preferred types of Authentic Materials among first-year English Language students at Saigon University (SGU). A mixed-methods approach, combining questionnaires and interviews, was employed to collect data from 100 freshmen for the survey and 10 for the interviews. The findings revealed a generally positive view towards Authentic Materials, perceiving them as beneficial for increasing engagement, enhancing vocabulary, and improving reading comprehension. Moreover, magazines, novels, and short stories were the preferred genres of Authentic Materials. However, challenges related to Authentic Materials, such as difficulty in relevance to course content, were also highlighted. In conclusion, Authentic Materials are perceived as both engaging and educationally valuable, despite some implementation challenges. This study contributes to the understanding of material selection in EFL contexts, offering evidence-based insights that can inform curriculum design and classroom practices in higher education.